Pengembangan Aplikasi Pembelajaran Bahasa Isyarat Berbasis Android Tablet - Maharoni Hendra Pradikja; Herman Tolle; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sign language is used in the daily lives of people with hearing and speech impaired. One of the difficulties is how the deaf can inform the sign language used and can be understood by people who can hear so deaf people can communicate, interact, socialize, make friends, and dialogue occurs in everyday social. Applications "PemBais" designed to help reduce the difficulties faced by the deaf and mute. Applications "PemBais" This provides a method of learning Indonesian Sign Language for the deaf and speech impaired quickly and practical for using the means of Android-based applications on smartphone devices. Applications Functional testing has been done with each of the test cases have been tested and properly, with the result declared all valid. Usability testing is obtained from a very satisfactory result for analysis of the application "PemBais" to achieve an average score of 87,18%.